(untitled) (Journal of Science and Engineering, 2026)
Historical structures that have endured for centuries present unique challenges for seismic assessment due to uncertainties in material properties, construction techniques, and the cumulative effects of past modifications and damage. Dealing with such complexity can be time-consuming and challenging. However, using a non-destructive vibration test for seismic assessment of the historical structure is a widely adopted and reliable method for understanding global behaviour. This study performed the ambient vibration tests of the Bhairabnath temple of Bhaktapur, Nepal, to investigate its dynamic characteristics. The vibration tests were conducted in the damaged and post-reconstruction phases. It shows the identified predominant frequency of X and Y direction of the structure in the damaged state are 1.51 and 2.29 Hz, respectively, slightly lower than the post-reconstruction state, which are 1.59 and 2.5 Hz, respectively. This reduction in the structural frequency is attributed to the reduction in the global stiffness, demonstrating the increased structural flexibility. In the post-reconstruction state, operational modal analysis was performed using enhanced frequency domain decomposition and stochastic subspace identification to obtain its dynamic characteristics. The reliability between the two techniques was evaluated using the cross-matrix assurance criteria, which demonstrate a strong correlation between the obtained frequencies and mode shapes. Similarly, the discrepancies in principal directions are 5.3% and 9.17% correspond to the different structural states, which indicate a reduction of 10% and 17% structural stiffness in the damaged state. Hence, the study underscores the significance of vibration test in determining the dynamic properties of the structure and highlights the necessity of structural health monitoring in historical structures.